Large-size bonding method for multi-stage sequential TiAl single crystals

By using vacuum diffusion bonding equipment to perform the bonding of parallel sheets and vertical sheets under high vacuum, combined with single-point diamond turning and chemical mechanical polishing, the growth and bonding problems of large-size TiAl single crystals are solved, and atomic diffusion bonding and recrystallization-free atomic bonding of large-size multi-order TiAl single crystals are achieved.

CN119507056APending Publication Date: 2025-02-25YANSHAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411715685.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult to grow large-size defect-free multi-stage TiAl single crystal rods, and the surface treatment and bonding methods of small-size TiAl single crystals are not suitable for large-size samples.

Method used

The vacuum diffusion bonding equipment is used to bond the large-size TiAl single crystal samples in a parallel sheet and a vertical sheet under high vacuum. The surface roughness of the sample is reduced by single-point diamond turning and chemical mechanical polishing, and the atomic diffusion bonding of the large-size TiAl single crystal is achieved.

Benefits of technology

A large-size multi-level sequence structure TiAl single crystal with a size of 60mm×20mm×30mm was successfully obtained, achieving atomic bonding without recrystallization, which is suitable for the application of complex components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507056A_ABST
    Figure CN119507056A_ABST
Patent Text Reader

Abstract

The invention discloses a large-size bonding method for multi-stage sequential TiAl single crystals, and belongs to the technical field of metal alloy welding. The invention provides a parallel lamella bonding method of a large-size multi-stage sequential TiAl single crystal. The method comprises the following steps: the surface roughness of a sample reaches below 200nm; and carrying out parallel lamellar orientation bonding by adjusting temperature, pressure and heat preservation time under a high vacuum degree. The invention also provides an atomic-scale diffusion bonding method of the large-size multi-stage sequential TiAl single crystal, which comprises the following steps of: after the parallel lamellae are subjected to oriented bonding, repeatedly placing under a high vacuum degree, and carrying out vertical lamellar oriented bonding by adjusting the temperature, the pressure and the heat preservation time, so as to obtain the large-size multi-stage sequential TiAl single crystal after the parallel lamellae and the vertical lamellae are bonded. According to the method, atomic-scale diffusion bonding of the large-size TiAl single crystal is achieved, and the size requirement of practical application is met. The operation method is simple, energy-saving and environment-friendly, and can be used for bonding in batches.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal alloy welding, and in particular relates to a process method for large-size bonding of multi-level sequenced TiAl single crystals. Background Art

[0002] TiAl alloy (density about 4g / cm 3 ) is gradually replacing nickel-based high-temperature alloys (density about 8.4g / cm 3 ) to reduce the weight of the engine itself to improve the thrust-to-weight ratio. The performance of the newly developed multi-level structure (Hierarchical oriented lamellar, HOL) TiAl single crystal is better than that of the TiAl-4822 alloy currently used. However, HOL-TiAl has a complex multiphase structure and reactivity, it is difficult to maintain a coherent interface, and it is difficult to control the solidification process. Compared with the more direct single-phase growth of nickel-based high-temperature alloys, these factors make the growth of large defect-free HOL-TiAl single crystals more challenging. Moreover, the equipment and processes required to grow large, high-quality HOL-TiAl single crystals are more expensive and less developed than those of nickel-based high-temperature alloys. Ultimately, it is impossible to grow HOL-TiAl single crystal rods with a diameter greater than 30 mm. In order to be able to apply it to complex components and expand its size and application range, it is necessary to conduct large-scale bonding experiments.

[0003] For example, the authorized invention patent with the prior art announcement number CN115928217B achieves the surface roughness of small-sized samples below 200nm through precision turning methods; by adjusting the welding parameters, the non-recrystallization atomic-level bonding of small-sized samples with parallel lamellar orientation is finally achieved, and a TiAl single crystal sample with a size of 8mm×6mm×8mm is obtained. However, this method is only effective for small-sized TiAl single crystal samples. During the precision turning process, the turning tool will wear out, resulting in limited ability to process the surface, and only precision turning can be performed on the bonding surface of 8mm×6mm and below. At present, there is no effective surface treatment and bonding method for large-sized (such as 60mm×20mm×30mm) TiAl single crystal samples, and the surface treatment and bonding methods of small-sized TiAl single crystals are not applicable to large-sized TiAl single crystals.

[0004] Therefore, the present invention improves the surface treatment method of large-sized TiAl single crystal samples, so that the surface of large-sized samples can achieve a low roughness effect. In addition, TiAl single crystals are bonded by parallel lamellae orientation and parallel and perpendicular lamellae orientation to obtain large-sized multi-level TiAl single crystal samples. Summary of the invention

[0005] In view of the defects existing in the above-mentioned prior art, in order to solve the technical problem that large-sized HOL-TiAl single crystal rods cannot be grown, the purpose of the present invention is to design and provide a large-sized atomic-level diffusion bonding process method for TiAl single crystals with efficient, stable process flow and batch reproducible production. The present invention uses vacuum diffusion bonding equipment to bond samples under high vacuum to obtain large-sized (30mm×20mm×30mm or 60mm×20mm×30mm) TiAl single crystals.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In one aspect, the present invention provides a parallel layer bonding method for a large-scale multi-level TiAl single crystal, comprising the following steps:

[0008] (1) Weighing a TiAl single crystal rod as a base material, cutting it into a large-sized sample to be welded, and performing rough turning and chemical mechanical polishing on the bonding surface of the sample to be welded to obtain a sample to be welded with a surface roughness of less than 200 nm;

[0009] (2) Place the above-mentioned sample to be bonded in the bonding equipment and evacuate it to a vacuum degree of 10 -4 Pa, after heating to 1000-1300°C, increase the pressure to 10-70MPa, keep at the highest temperature for 5-20h, cool to room temperature with the furnace, and obtain large-sized multi-level TiAl single crystals after parallel layer bonding.

[0010] In the parallel lamellar bonding method of a large-sized multi-level TiAl single crystal, the large size in step (1) is (10-30 mm)×(10-20 mm)×(5-15 mm).

[0011] The parallel lamellar bonding method of a large-size multi-level TiAl single crystal is described, and the cutting method is diamond wire cutting.

[0012] In the parallel lamellar bonding method of a large-size multi-level TiAl single crystal, the heating rate during the heating process is 5 to 20° C. / min.

[0013] In a second aspect, the present invention provides a large-sized multi-level ordered TiAl single crystal prepared by any of the methods described above.

[0014] In a third aspect, the present invention provides an atomic-level diffusion bonding method for a large-sized multi-level TiAl single crystal, comprising the following steps:

[0015] (1) Weighing a TiAl single crystal rod as a base material, cutting it into a large-sized sample to be welded, and performing rough turning and chemical mechanical polishing on the bonding surface of the sample to be welded to obtain a sample to be welded with a surface roughness of less than 200 nm;

[0016] (2) Place the above-mentioned sample to be bonded in the bonding equipment and evacuate it to a vacuum degree of 10 -4 Pa, after heating to 1000-1300°C, increase the pressure to 10-70MPa, keep the temperature at the highest temperature for 5-20h, cool to room temperature with the furnace, and obtain a sample after parallel sheet bonding;

[0017] (3) The surface to be bonded of the sample after parallel layer bonding is subjected to rough turning and chemical mechanical polishing to a surface roughness of less than 200 nm, and then placed in a bonding device and evacuated to a vacuum degree of 10 -4 Pa, after heating to 1000-1300°C, increase the pressure to 10-70MPa, keep at the highest temperature for 5-20h, cool to room temperature along with the furnace, and obtain a large-sized multi-level TiAl single crystal with both parallel layers and vertical layers bonded.

[0018] In the atomic-level diffusion bonding method of a large-sized multi-level TiAl single crystal, the large size in step (1) is (10-30 mm)×(10-20 mm)×(5-15 mm).

[0019] In the atomic-level diffusion bonding method for large-sized multi-level TiAl single crystals, the heating rates during the heating processes in steps (2) and (3) are both 5 to 20° C. / min.

[0020] In a fourth aspect, the present invention provides a large-sized multi-level ordered TiAl single crystal prepared by any of the methods described above.

[0021] In a fifth aspect, the present invention provides the use of the large-sized multi-level ordered TiAl single crystal as an engine raw material.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention reduces the roughness of the surface of a large-size sample (30mm×20mm) by combining single-point diamond turning and chemical mechanical polishing; the sample is bonded in parallel and perpendicular lamellae orientation under high vacuum, effectively isolating the contact between oxygen and the bonding surface; and the bonded TiAl single crystal with a size of 60mm×20mm×30mm is finally obtained by adjusting the temperature and pressure, which meets the size requirements of practical applications. The present invention has a simple operation method, low cost, and can be prepared in large quantities. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of sample size prepared by wire cutting, where (a) is a schematic diagram of single crystal rod orientation; (b) is a dimensional diagram of parallel lamellae sample;

[0025] Figure 2 The surface roughness test results of the surface to be bonded of the sample after surface treatment, where (a) is the surface roughness of one of the surfaces to be bonded; (b) is the surface roughness of the other surface to be bonded; (c) is the undulation of the two surfaces to be bonded;

[0026] Figure 3 Schematic diagram of parallel sheet sample bonding, where (a) is a schematic diagram of two samples to be bonded, and the surface marked with a red frame is the surface to be bonded; (b) is a schematic diagram of the sample after bonding;

[0027] Figure 4 Schematic diagram of EBSD characterization of the bonding interface of a parallel lamellae oriented sample kept at 1000℃ for 5h under 10MPa pressure, where (a) is the IPF-Y image of the bonding interface; (b) is the phase image of the bonding interface;

[0028] Figure 5 Schematic diagram of vertical sheet sample bonding, where (a) is a schematic diagram of two samples to be bonded, and the surface marked with a red frame is the surface to be bonded; (b) is a schematic diagram of the bonded state sample obtained after bonding;

[0029] Figure 6 Schematic diagram of EBSD characterization of the bonding interface of a vertically oriented sample heated at 1000°C for 5 h under 10 MPa pressure, where (a) is the BC diagram of the bonding interface; (b) is the IPF-Y diagram of the bonding interface; (c) is the phase diagram of the bonding interface;

[0030] Figure 7 Schematic diagram of EBSD characterization of the bonding interface of a parallel lamellae oriented sample kept at 1400℃ for 30h under 80MPa pressure, where (a) is the IPF-Y image of the bonding interface; (b) is the phase image of the bonding interface;

[0031] Figure 8 Schematic diagram of EBSD characterization of the bonding interface of a vertically oriented sample kept at 1400℃ for 30h under 80MPa pressure, where (a) is the BC diagram of the bonding interface; (b) is the phase diagram of the bonding interface; (c) is the IPF-X diagram of the bonding interface; and (d) is the IPF-Y diagram of the bonding interface. DETAILED DESCRIPTION

[0032] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0033] Embodiment 1:

[0034] (1) First, a bonding experiment was conducted on a TiAl single crystal rod sample with parallel lamellar orientation. The sample was prepared into a 30 mm × 20 mm × 15 mm sample to be welded using diamond wire cutting. Figure 1 Schematic diagram of sample dimensions prepared for wire cutting.

[0035] (2) The surface to be bonded (30 mm × 20 mm) of the sample was then rough turned and chemically mechanically polished using a single-point diamond lathe to reduce the surface roughness Sa to less than 200 nm. The specific steps are as follows:

[0036] The turning tool feed rate was 1 μm, and only one rough turning was performed on the surface. The turned samples were then chemically mechanically polished using a polyurethane disc. The polishing liquid used was alkaline SiO 2 Suspension, dripping rate is 2ml / min.

[0037] The process is as follows:

[0038] 1) Rough grinding: the spindle speed is 30 rpm, the driving shaft and dressing shaft speed are 25 rpm, and it lasts for 1 hour.

[0039] 2) Fine grinding: The speed of the main shaft, driving shaft and dressing shaft are all reduced to 10 rpm and last for 1 hour.

[0040] 3) Fine grinding: The speed of each axis is reduced to 5 rpm and the duration is 2 hours.

[0041] The surface roughness Sa of the bonding surface of the sample after the above surface treatment was measured by white light interferometry. The results are as follows: Figure 2 As shown in the figure, the surface roughness Sa of the two surfaces to be bonded are 35nm and 83nm respectively, which meets the requirement of making the surface roughness Sa below 200nm. Thanks to the combination of turning and chemical mechanical polishing, turning obtains a good surface shape (with very small fluctuations within 50nm), and chemical mechanical polishing reduces the surface roughness, ultimately making the surface roughness of large-sized TiAl single crystal samples reach below 200nm, or even below 100nm.

[0042] (3) Place the prepared sample into the bonding equipment and turn on the mechanical pump and molecular pump to evacuate the sample until the vacuum reaches 10 -4 Pa. Then, the temperature is raised to 1000℃ at a heating rate of 20℃ / min. After the temperature reaches the set value, the pressure is increased to 10MPa, and the temperature is kept at the highest temperature (i.e. 1000℃) for 5h, and then cooled with the furnace. Figure 3 Figure 1 is a schematic diagram of parallel lamellar sample bonding. Figure 4 The bonding effect is shown, and it can be seen that the final sample achieves recrystallization-free atomic-level bonding.

[0043] Embodiment 2:

[0044] The parallel-lamella orientation bonded sample obtained in Example 1 was subjected to a bonding experiment with a perpendicular-lamella orientation. The surface to be bonded (30 mm × 20 mm) of the sample was rough turned and chemically mechanically polished using a single-point diamond lathe to achieve a surface roughness Sa of less than 200 nm. The specific methods of rough turning and chemically mechanical polishing were the same as those in the above example. The surface roughness S of the surface to be bonded of the sample after the above surface treatment was measured using a white light interferometer. The results showed that the surface roughness Sa of the two surfaces to be bonded were 68 nm and 94 nm, respectively, which met the requirement of achieving a surface roughness Sa of less than 200 nm.

[0045] Place the prepared sample into the bonding equipment, and turn on the mechanical pump and molecular pump to evacuate the sample until the vacuum reaches 10 -4 Pa. Then, the temperature is raised to 1000℃ at a heating rate of 20℃ / min. After the temperature reaches the set value, the pressure is increased to 10MPa, and the temperature is kept at the highest temperature (i.e. 1000℃) for 5h, and then cooled with the furnace. Figure 5 The figure is a schematic diagram of the bonding of vertical slice samples, with dimensions of 60mm×20mm×30mm. Figure 6 The bonding effect is shown, and it can be seen that the final sample achieves recrystallization-free atomic-level bonding.

[0046] Both the samples with parallel lamellae orientation and the samples with perpendicular lamellae orientation achieved recrystallization-free atomic-level bonding, and finally a large-sized bonded sample with a size of 60mm×20mm×30mm was obtained.

[0047] Embodiment 3:

[0048] (1) First, a bonding experiment was carried out on a TiAl single crystal rod sample with parallel lamellar orientation. The sample was prepared into a 30 mm × 20 mm × 15 mm sample to be welded using diamond wire cutting.

[0049] (2) The surface to be bonded (30 mm × 20 mm) of the sample is rough turned and chemically mechanically polished using a single-point diamond lathe to achieve a surface roughness Sa of less than 200 nm. The specific methods for rough turning and chemical mechanical polishing are the same as those in Example 1 above.

[0050] (3) Place the prepared sample into the bonding equipment and turn on the mechanical pump and molecular pump to evacuate the sample until the vacuum reaches 10 -4 Pa or less. Then the temperature was raised to 1300°C at a heating rate of 5°C / min. After the temperature reached the set value, the pressure was increased to 70MPa, and the temperature was kept at the highest temperature point (i.e. 1300°C) for 20 hours. The sample (30mm×30mm×20mm) after parallel sheet bonding was obtained.

[0051] Embodiment 4:

[0052] The parallel-lamellar-oriented bonding sample obtained in Example 3 was subjected to a perpendicular-lamellar-oriented bonding experiment. The surface to be bonded (30 mm×20 mm) of the sample was rough-turned and chemically mechanically polished using a single-point diamond lathe to achieve a surface roughness Sa of less than 100 nm. The specific methods of rough-turning and chemically mechanical polishing were the same as those in Example 1.

[0053] Place the prepared sample into the bonding equipment, and turn on the mechanical pump and molecular pump to evacuate the sample until the vacuum reaches 10 -4 Then the temperature was raised to 1300°C at a heating rate of 5°C / min. After the temperature reached the set value, the pressure was increased to 70MPa, and the temperature was kept at the highest temperature (i.e. 1300°C) for 20 hours, and then cooled with the furnace.

[0054] The bonding effect is the same as that in Example 2, both the samples with parallel lamellae orientation and the samples with perpendicular lamellae orientation achieve recrystallization-free atomic-level bonding.

[0055] Comparative Example 1:

[0056] First, the bonding experiment was carried out on the sample with parallel lamella orientation. The sample was prepared into a 30mm×20mm×15mm sample to be welded using diamond wire cutting. Then, the surface to be bonded (30mm×20mm) was rough turned and chemically mechanically polished using a single-point diamond lathe to make the surface roughness Sa reach below 200nm. The prepared sample was placed in the bonding equipment, and the mechanical pump and molecular pump were turned on in turn to evacuate until the vacuum reached 10 -4 Pa. Then the temperature was raised to 900°C at a heating rate of 20°C / min. After the temperature reached the set value, the pressure was increased to 5MPa, and the temperature was kept at the highest temperature for 1h, and then cooled with the furnace.

[0057] Due to inappropriate bonding parameters, the samples with parallel lamellae orientation did not achieve bonding, and the next step of bonding experiments on samples with perpendicular lamellae orientation could not be carried out.

[0058] Comparative Example 2:

[0059] First, a bonding experiment was conducted on the sample with parallel lamellar orientation. The sample was prepared into a 30mm×20mm×15mm sample to be welded using diamond wire cutting. The surface to be bonded (30mm×20mm) of the sample was then rough turned and chemically mechanically polished using a single-point diamond lathe to reduce the surface roughness Sa to less than 200nm. The prepared sample was placed in the bonding equipment, and the mechanical pump and molecular pump were turned on in turn to evacuate until the vacuum reached 10 -4Pa. Then the temperature was raised to 1400℃ at a heating rate of 20℃ / min. After the temperature reached the set value, the pressure was increased to 80MPa, and the temperature was kept at the highest temperature for 30 hours, and then cooled with the furnace. Figure 7 As shown, it can be seen that due to the influence of excessive pressure and temperature during the bonding process, the final bonding mode of the sample is recrystallization bonding, and recrystallization-free atomic-level bonding cannot be achieved.

[0060] Subsequently, the samples bonded in parallel lamellar orientation were subjected to bonding experiments in perpendicular lamellar orientation. The surface to be bonded (30 mm × 20 mm) of the sample was rough turned and chemically mechanically polished using a single-point diamond lathe to reduce the surface roughness Sa to less than 200 nm. The prepared sample was placed in the bonding equipment, and the mechanical pump and molecular pump were turned on in turn to evacuate until the vacuum reached 10 -4 Pa. Then the temperature was raised to 1400℃ at a heating rate of 20℃ / min. After the temperature reached the set value, the pressure was increased to 80MPa, and the temperature was kept at the highest temperature for 30 hours, and then cooled with the furnace. Figure 8 As shown, it can be seen that due to the influence of excessive pressure and temperature during the bonding process, both the parallel lamellae orientation and the perpendicular lamellae orientation of the final sample were recrystallized, and recrystallization-free atomic-level bonding was not achieved.

Claims

1. A parallel layer bonding method for large-scale multi-level TiAl single crystals, characterized in that: The following steps are involved: (1) Weighing a TiAl single crystal rod as a base material, cutting it into large-sized samples to be welded, and performing rough turning and chemical mechanical polishing on the bonding surface of the sample to be welded to obtain a sample to be welded with a surface roughness of less than 200 nm; (2) Place the above-mentioned sample to be bonded in the bonding equipment and evacuate it to a vacuum degree of 10 -4 Pa, after heating to 1000-1300°C, increase the pressure to 10-70MPa, keep at the highest temperature for 5-20h, cool to room temperature with the furnace, and obtain large-sized multi-level TiAl single crystals after parallel layer bonding.

2. A parallel lamellar bonding method for a large-sized multi-level TiAl single crystal as claimed in claim 1, characterized in that: The large size described in step (1) is (10-30 mm)×(10-20 mm)×(5-15 mm).

3. A parallel lamellar bonding method for a large-sized multi-level TiAl single crystal as claimed in claim 1, characterized in that: The cutting method is diamond wire cutting.

4. A parallel lamellar bonding method for a large-sized multi-level TiAl single crystal as claimed in claim 1, characterized in that: The heating rate during the heating process is 5 to 20° C. / min.

5. A large-sized multi-level TiAl single crystal prepared by the method according to any one of claims 1 to 4.

6. An atomic-level diffusion bonding method for large-scale multi-level TiAl single crystals, characterized in that: The following steps are involved: (1) Weighing a TiAl single crystal rod as a base material, cutting it into large-sized samples to be welded, and performing rough turning and chemical mechanical polishing on the bonding surface of the sample to be welded to obtain a sample to be welded with a surface roughness of less than 200 nm; (2) Place the above-mentioned sample to be bonded in the bonding equipment and evacuate it to a vacuum degree of 10 -4 Pa, after heating to 1000-1300°C, increase the pressure to 10-70MPa, keep the temperature at the highest temperature for 5-20h, cool to room temperature with the furnace, and obtain a sample after parallel sheet bonding; (3) The surface to be bonded of the sample after parallel layer bonding is subjected to rough turning and chemical mechanical polishing to a surface roughness of less than 200 nm, and then placed in a bonding device and evacuated to a vacuum degree of 10 -4 Pa, after heating to 1000-1300°C, increase the pressure to 10-70MPa, keep at the highest temperature for 5-20h, cool to room temperature along with the furnace, and obtain a large-sized multi-level TiAl single crystal with both parallel layers and vertical layers bonded.

7. The atomic level diffusion bonding method of a large-sized multi-level structured TiAl single crystal according to claim 1, characterized in that: The large size described in step (1) is (10-30 mm)×(10-20 mm)×(5-15 mm).

8. The atomic level diffusion bonding method of a large-sized multi-level structured TiAl single crystal according to claim 1, characterized in that: The heating rates during the heating process in steps (2) and (3) are both 5 to 20°C / min.

9. A large-sized multi-level TiAl single crystal prepared by the method according to any one of claims 6 to 8.

10. Use of the large-sized multi-level structured TiAl single crystal as claimed in claim 5 or 9 as an engine raw material.

Citation Information

Patent Citations

  • Bonded TiAl single crystal and diffusion bonding process thereof

    CN115928217B

  • Lamellar orientation completely controllable TiAl single crystal alloy and preparation method thereof

    CN104328501A

  • Method for improving direct bonding strength of silicon carbide

    CN109904064A

  • Bonding-state TiAl single crystal and diffusion bonding process method thereof

    CN115928217A

  • Diamond single crystal homogeneous bonding method

    CN118773734A